2020
DOI: 10.3390/met10010123
|View full text |Cite
|
Sign up to set email alerts
|

Reducing-Effect of Chloride for the Dissolution of Black Copper

Abstract: Oxidized black copper ores are known for their difficulty in dissolving their components of interest through conventional methods. This is due to its non-crystalline and amorphous structure. Among these minerals, copper pitch and copper wad are of great interest because of their considerable concentrations of copper and manganese. Currently, these minerals are not incorporated into the extraction circuits or left untreated, whether in stock, leach pads, or waste. For the recovery of its main elements of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…In the investigations carried out by Benavente et al, [18] and Pérez et al, [16] it was discovered that working in an acid-reducing leaching favors dissolution of MnO2, thus favoring the extraction of copper. Subsequently, Torres et al, [17] demonstrated that it is possible to considerably increase concentrations of Cu and Mn in solutions obtained from black copper in short periods of time (20 min) when working in stirred reactors and carrying out pre-treatment processes (agglomeration and curing) by adding a reducing agent (NaCl in that study). Furthermore, it should be noted that various studies have been carried out with the aim of MnO2 dissolution from manganese nodules [20][21][22][23][24][25][26][27][28], which provided multiple alternatives for extraction of Mn and Cu from black copper, as they have are similarly processed in leaching systems.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…In the investigations carried out by Benavente et al, [18] and Pérez et al, [16] it was discovered that working in an acid-reducing leaching favors dissolution of MnO2, thus favoring the extraction of copper. Subsequently, Torres et al, [17] demonstrated that it is possible to considerably increase concentrations of Cu and Mn in solutions obtained from black copper in short periods of time (20 min) when working in stirred reactors and carrying out pre-treatment processes (agglomeration and curing) by adding a reducing agent (NaCl in that study). Furthermore, it should be noted that various studies have been carried out with the aim of MnO2 dissolution from manganese nodules [20][21][22][23][24][25][26][27][28], which provided multiple alternatives for extraction of Mn and Cu from black copper, as they have are similarly processed in leaching systems.…”
Section: Introductionmentioning
confidence: 85%
“…Black copper minerals are abundant in Chile, being present in large deposits such as: Mina sur Chuquicamata, Damiana in El Salvador, Lomas Bayas Spence, and El Tesoro and Huanquintipa in Collahuasi [16]. Even though these minerals contain considerable amounts of Cu and Mn [17], they are not commonly incorporated in the leach pads, being considered waste [18]. This is due to its amorphous, which prevents treating these mineral resources by means of conventional hydrometallurgical processes [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within copper extractive processes, flotation is the most widely used worldwide, producing 80 % of the production of this commodity [3][4][5][6][7]. Flotation processes are a recurring alternative in the treatment of copper sulfide minerals, since the selective separation of minerals is achieved, based on their hydrophobic and hydrophilic properties [8][9][10].…”
Section: Introductionmentioning
confidence: 99%